2007
DOI: 10.1128/aem.00315-07
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics and Metabolite Target Analysis of Lactic Acid Bacteria during Laboratory Fermentations of Wheat and Spelt Sourdoughs

Abstract: Four laboratory sourdough fermentations, initiated with wheat or spelt flour and without the addition of a starter culture, were prepared over a period of 10 days with daily back-slopping. Samples taken at all refreshment steps were used for determination of the present microbiota. Furthermore, an extensive metabolite target analysis of more than 100 different compounds was performed through a combination of various chromatographic methods including liquid chromatography-mass spectrometry and gas chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
149
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 188 publications
(174 citation statements)
references
References 66 publications
13
149
2
4
Order By: Relevance
“…All strains from this study were able to tolerate pH 3.0 with a survival percentage of more than 70%, and therefore they can be considered as acidtolerant LAB strains. This tolerance capacity of lactic acid bacteria warranted the production of various antimicrobial substances which might create unfavorable conditions for the growth of pathogens as well as toxigenic and spoilage organisms in humans and/or animals (van der Meulen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…All strains from this study were able to tolerate pH 3.0 with a survival percentage of more than 70%, and therefore they can be considered as acidtolerant LAB strains. This tolerance capacity of lactic acid bacteria warranted the production of various antimicrobial substances which might create unfavorable conditions for the growth of pathogens as well as toxigenic and spoilage organisms in humans and/or animals (van der Meulen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Culture-dependent approaches represent the only means of recovering microorganisms from the fermented substrate [50], although it is widely recognized that they do not allow analysis of true diversity and/or population dynamics [3,49,58]. On the other hand, various studies have shown that culture-independent approaches, such as denaturing gradient gel electrophoresis of 16S rRNA gene amplicons (PCR-DGGE), provide a more reliable and reproducible means for studying microbial populations in complex food ecosystems [9,16,65,75].…”
Section: E Madoroba Et Al / Systematic and Applied Microbiology XXXmentioning
confidence: 99%
“…PCR was performed as described previously [75] on a MyCycler TM thermal cycler (BioRad, Hercules, USA). The 16S rRNA V3 region was also amplified from 13 different bacterial reference strains, and the resulting amplicons were combined for use as a DGGE reference standard [75].…”
Section: Pcr-dggementioning
confidence: 99%
See 2 more Smart Citations